Neuroimaging personality, social cognition, and character - Absher, John R.; Cloutier, Jasmin; ScienceDirect eBooks (London : Academic Press, 2016)
Neuroimaging Personality, Social Cognition, and Character covers the science of combining brain imaging with other analytical techniques for use in understanding cognition, behavior, consciousness, memory, language, visual perception, emotional control, and other human attributes. Multidimensional brain imaging research has led to a greater understanding of character traits such as honesty, generosity, truthfulness, and foresight previously unachieved by quantitative mapping. This book summarizes the latest brain imaging research pertaining to character with structural and functional human brain imaging in both normal individuals and those with brain disease or disorder, including psychiatric disorders. By reviewing and synthesizing the latest structural and functional brain imaging research related to character, this book situates itself into the larger framework of cognitive neuroscience, psychiatric neuroimaging, related fields of research, and a wide range of academic fields, such as politics, psychology, medicine, education, law, and religion.
Introduction -- Perspectives on the neural basis of personality and dispositions -- Brain imaging perspectives on understanding the self and others: from perception to social cognition -- Brain imaging perspectives on affect and emotional regulation -- Brain imaging perspectives on the basis of prosociability -- Brain imaging and society.
Includes bibliographical references and index.
Description based on print version record.
Elsevier
Keywords: Brain -- Imaging; Head -- Imaging; Character; MEDICAL / Physiology; SCIENCE / Life Sciences / Human Anatomy & Physiology; Brain -- Imaging; Character; Head -- Imaging; Electronic books